Влияние художественной системы и жанровых особенностей на членение романа У. Теккерея «Ярмарка тщеславия» и отражение этого членения в переводе - Харченко, А.Л.; Харченко, О.В. (Культура народов Причерноморья, 2013)
В статье рассматривается влияние жанра произведения на характер перераспределения
границ абзацев при переводе с английского языка на русский.В настоящее время в разделах
грамматической науки о синтаксисе вопросы о знаковом характере «красной строки», вопросы
членения текста на абзацы почти не освещены. При проведении исследования был использован метод
сравнительного анализа.
Ключевые слова: художественная система, сверхфразовое членение текста, жанр, перераспределение
границ абзацев, типы абзацев. У статті розглядається вплив жанру твору на характер перерозподілу меж абзаців при
перекладі з англійської мови на російську.В даний час в розділах граматичної науки про синтаксис
питання про знаковий характер «нового рядка», питання членування тексту на абзаци майже не
висвітлені. При проведенні дослідження був використаний метод порівняльного аналізу.
Ключові слова: художня система, понадфразове членування, жанр, перерозподіл меж абзаців, типи
абзаців. The investigation of the text of the novel from the point of view of its division into paragraphs,
peculiarities of “the indented line”, the analysis of the types of the passages and their functioning in the original
and translated texts is done in the article. The influence of the genre of the novel on the rearrangement of the
paragraphs in the translated into Russian text is investigated. It is pointed out that the division of the text into
paragraphs depends upon the peculiarities of the art system. But not only the peculiarities of the art system and
the individual style of the author influence the division of the art text. One of the main features of the novel of
critical realism is the unlimited presence of the author and his position in the novel. The author’s commentary in
the novel “Vanity Fair” makes an organic part of the style of the author. The paragraph with the author’s
commentary is extremely emotional. The “indented line” here is an additional means of expressivity. The method
of comparative analysis was used in the research. At present, the issues about the meaning and functional
character of “the indented line” are not studied well enough. However, the peculiarities of the functioning of
“the indented line” give great opportunities to the perfection of the science about punctuation of the language.
The study of the peculiarities of the functioning of “the indented line” gives the interpreter and the reader the
opportunity to comprehend this or that literary work in a more adequate way.
Key words: hyper syntactical division of the text, genre, rearrangement of the paragraphs, types of passages.